Karakteristik Diakritik Mushaf Magribi, Arab Saudi, dan Indonesia: - Achmad Faizur Rosyad (SUHUF, 2015)
This study is based on a writer thought that there are many mushafs, what the most moslem people read them, have a differences diacritics. The basic differences are signing hija'iyah with dots, signing vocal and tajwiâ—„d reading technic or called shakl, and signing technic of waqf and ibtida'. The problems that the writer want to reveal are (i) why all mushafs called having a same rasm, that is a Rasm Usmani, whereas they have a differences signs and diacritics. (ii) Why they have a differences diacritizations if their sumber are same. (iii) How are the diacritizations made in the three of the mushafs. From this study, Magribi Mushaf has a same sign form with Saudi Arabian more than Indonesian, with their own references. Indonesian Mushaf has a same sign location with Saudi Arabian more than Magribi. Keyword: Magribi, Masyriqi, Mushaf, i'jam, tasykil.